Health behaviors and health locus of control in patients with epilepsy - Staniszewska, Anna; Olejniczak, Dominik; Dąbrowska-Bender, Marta (Journal of Education, Health and Sport, 2017)
Objective: The aim of the study was to show the relation between health behavior and preferred health locus of control in epileptic patients. Material and methods: One hundred and ninety six participants gave their answers to the Polish version of the Multidimensional Health Locus of Control questionnaire version B and Health Behavior Inventory. Results: Among all dimensions of health locus of control, the respondents obtained the highest scores in the dimension of internal control (26.0±8.2), and the lowest ones in the dimension of external control (18.0±5.5). The average score for health behaviors was (88.0±11.0). In the category of prophylactic behaviors the highest scores were (23.0±3.6). The category of health practices received the lowest number of points (21.0±3.5). The internal dimension of health control showed a strong significant correlation with the following categories: health behaviors (P=0.00), proper nutrition habits (P=0.00), and positive psychological attitude (P=0.002). The external dimension of health control showed a low significant correlation with health behaviors and prophylactic behaviors (P=0.05). The chance dimension of health control did not show any significant correlations with health behaviors and their categories (P>0.05 in all cases). Conclusion: Our results demonstrate that the participants believed to have more control over their health than other people or chance did. Sociodemographic and clinical factors did not influence health locus of control in patients with epilepsy.